1959
DOI: 10.1111/j.1365-2621.1959.tb17642.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE STUDIES ON MEDIA FOR COUNTING ANAEROBIC BACTERIAL SPORESa

Abstract: Investigations described in this paper are related entirely to the recovery of viable spores of PA-3679 and Clostridium botulinum type B. Spores of the respective test organisms were subjected to thermal treatment and gamma radiation independently. Questionnaires were distributed in January, 1957, to 26 individuals at various laboratories whose personnel have been interested in spore recovery after exposure to either heat and/or radiation. Information relative to recovery media used in counting anaerobes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

1961
1961
1978
1978

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
1
15
1
Order By: Relevance
“…Moreover, differences between species, and even strains, make generalizations almost impossible. In an interlaboratory survey (Wheaton, Pratt & Jackson, 1959)) pork-pea infusion and beef infusion gave the highest counts of severely heated spores of Putrefactive Anaerobe PA 3679 and Cl. botulinum type B. Mildly heated spores grew equally well in pork-pea infusion and a Tryptone-yeast extract medium.…”
Section: (B) Recovey Mediamentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, differences between species, and even strains, make generalizations almost impossible. In an interlaboratory survey (Wheaton, Pratt & Jackson, 1959)) pork-pea infusion and beef infusion gave the highest counts of severely heated spores of Putrefactive Anaerobe PA 3679 and Cl. botulinum type B. Mildly heated spores grew equally well in pork-pea infusion and a Tryptone-yeast extract medium.…”
Section: (B) Recovey Mediamentioning
confidence: 93%
“…Different viable counts of undamaged spores are frequently obtained if different counting media are used: this being particularly true in liquid media (see Riemann 1957;Wheaton, Pratt & Jackson, 1959;Riemann, 1960) (see Table 3).…”
Section: (B) Recovey Mediamentioning
confidence: 99%
“…Sterile brain heart infuSion broth, pork-pea infusion medium (Wheaton, 1959), fluid thioglycollate medium and trypticase soy broth (BBL) were used. Each series of tubes contained 0, 3.75, 7.5, 15, 30, or 45.6 ppm tylosin in 25 ml.…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggested that the present work should be based on strains of PA3679 from other laboratories to compare their ability to initiate outgrowth on various media with that of the stock strain of this laboratory as already reported in the first publication (Wheaton et al, 1959). To broaden the coverage of media, six additional media suggested in 1957 were added to the ten employed with heat-processed spores of PA3679.…”
Section: Subculturementioning
confidence: 96%
“…The first paper (Wheaton et al, 1959) under the present title was presented at the 1958 annual meeting of the Institute of Food Technologists. It gives the background for comparison of results on media used by some 26 university, government, and industry laboratories for recovery and counting of anaerobic spores.…”
Section: Subculturementioning
confidence: 99%